The Use of ClassIn Platform through Situational Approach for English Grammar Achievement of Grade 5 Chinese Students - Yao, Chen; Sakulwongs, Nipaporn (Journal of Research and Curriculum Development, 2025)
This study is devoted to compare grade 5 Chinese students English grammar achievement before and after using ClassIn platform through Situational approach. And also, to study grade 5 Chinese students' learning satisfaction towards using ClassIn platform through Situational approach. The study used a cluster random sampling method to select a sample of 30 grade 5 students from an elementary school in Xi'an, Shaanxi Province. The tools used in the study included lesson plans, grammar achievement tests and questionnaires. Three experts were invited to verify the validity of the research tools with IOC index, and the ranges from -1 to +1. The study used the pre-test and post-test as quantitative data and the questionnaire to collect qualitative data. The pre-test and post-test analyses of grammar scores were used to check the students' grammar scores, and the questionnaire was used to study the students' satisfaction. The results showed that there was a significant difference between pre-test scores and post-test scores, with a mean score of 3.70 on the pre-test and 12.53 on the post-test, with a mean difference of 8.83. The significance (p) value was less than .01, which indicated that teaching English grammar using ClassIn Platform through Situational approach is very effective. Moreover, the results of the questionnaire showed that the students were very satisfied that using ClassIn Platform through Situational approach in their English grammar classes. Therefore, the results of the study indicated that using ClassIn Platform through Situational approach is effective in improving the English grammar achievement of grade 5 Chinese students.